ANALISIS PERENCANAAN DAN PENGENDALIAN ANGGARAN PADA USAHA MIKRO MINUMAN KOPI: STUDI KASUS KOPI JAJJAN - Nur Eliza Siregar; Meyla Dwi Bastina; Azzahra Dinda Aulia; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the preparation of a sales budget as a financial planning and control tool in the Kopi Jajjan business. The sales budget plays an important role in helping business owners determine sales targets, estimate revenue, and support managerial decision-making. This research uses a descriptive quantitative approach with a case study of Kopi Jajjan. The data consist of sales data, demand projections, and revenue estimates prepared on a monthly and quarterly basis. The results show that a systematic sales budget provides a more structured financial overview, improves business planning efficiency, and helps anticipate market uncertainty risks. Through the implementation of a sales budget, Kopi Jajjan is able to plan business strategies more effectively and sustainably. This study is expected to serve as a reference for MSMEs in preparing sales budgets as a foundation for business financial management